HLA polymorphism in Israel. 9. An overall comparative analysis. - Bonné-Tamir, B; Bodmer, J; Bodmer, W; Pickbourne, P; Brautbar, C; Gazit, E; Nevo, S; Zamir, R (1978)
HLA gene frequencies in 11 Israeli populations and nine other relevant populations were used to calculate genetic distances in a quantitative assessment of their similarities and differences. The shortest distance found is between Polish and Rumanian Jews, while the largest is between Russian Jews and Black Africans. Estimates of "average" distances within major population groups suggest that the Ashkenazi Jews (Poles, Russians, Rumanians and Germans) are a more homogeneous population than East European non-Jews or than Middle-Eastern populations (Arabs, Armenians, Lebanese and Turks). A cline of distances between Ashkenazi Jews and other Jewish communities parallels their geographic distribution; however, the relatively large distance between the two North African communities (Libyans and Moroccans) demonstrates that geographic proximity is not necessarily correlated with genetic similarity. The Jewish populations, especially the Ashkenazi, show a clear divergence from their neighboring non-Jewish populations, among whom they have lived for many centuries. There are indications in the HLA data of a common origin for the diverse Jewish populations.